Lirica e poesia - Mazzarella, Eugenio (Bollettino Filosofico, 2017)
It was Leopardi who produced the thesis that «Lyric can be called the height the culmination the summit of poetry», and as such «the summit of human language» and «of the three main genres of poetry, the only one that really remains for the moderns». This primacy of lyric poetry rests in its ability to guard, better than epic and dramatic poetry, the linguistic institution of the world, the truth of being in the world as truth of word (Martin Heidegger). Lyrical expression as feeling and contemplation of oneself and one's being in the world expresses, each time, individually, the universal human, the original proclivity, in the word, in the ego, on the world. Lyric as the summit of poetry is like a summit reached. Like consciousness (in the evolutionary thesis of Julian Jaynes), poetry also has a story that takes place in the lyric phenomenon.